ANALISIS KELAYAKAN FINANSIAL USAHA SAPI PERAH SENTULFRESH INDONESIA DI KABUPATEN BOGOR - Siska Aprilia; Fembriarti Erry Prasmatiwi; Achdiansyah Sulaiman (Lampung University, 2021)
This research seeks to analyze the feasibility of dairy cattle business. This research was conducted in Sentulfresh Indonesia in Bogor Regency. Respondents consisted of the owner and the employees of dairy farm also yoghurt production. Data were analyzed by quantitatively using measurement criteria of financial viability and sensitivity analyzes. The results showed that dairy cattle business is financially viable as indicated by NPV values of Rp5,542,458,138.00; Net B/C values of 2.42; Gross B/C values of 1.63; IRR values of 35.09 percent; and PP of 5.76 from the economic life of dairy cattle for eight years, and dairy cattle business is still viable despite the drop in yoghurt sales of 6.24 percent, the drop in milk sales of 45.60 percent, and an increase in cow maintenance cost of 5.88 percent.Key words: dairy cattle, financial feasibility, sensitivity.